Enhancing commit message quality in software capstone projects with generative AI - Andrés Neyem; Agustín Rios-Letelier; Kevin Céspedes-Arancibia; Juan Pablo Sandoval Alcocer; Marcelo Mendoza (SoftwareX)
Software Capstone Projects provide valuable hands-on experience for students in software development, and creating effective commit messages is an essential, though often challenging, part of this process. These messages play a key role in managing repositories, facilitating collaboration, and offering insights into the project’s progression for mentors and managers. However, creating high-quality commit messages can be challenging, especially for novice developers. We introduce LetsCommit, a tool designed to improve the traditional Git commit command line interface. The tool utilizes three state-of-the-art Large Language Models (LLMs): GPT-3.5, GPT-4, and LLaMa-2, to provide commit message suggestions to students. Results from a user experience survey showed high satisfaction, indicating strong potential for incorporating LetsCommit into future projects. Beyond its technical applications, LetsCommit possesses transformative potential in the field of education. The iterative learning process it supports, coupled with real-time insights, reinforces good software development practices and enhances the overall learning experience. These findings highlight LetsCommit’s substantial impact on software engineering education, setting the stage for further advancements.